Tinjauan Maqashid Syariah Terhadap Penyedia Layanan Jasa Lampu dan Sound System di Propertys Yogyakarta - Imam Kamaluddin; Noval Hasbi; Muhammad Rafli Zidan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
As a Muslim entrepreneur, it is obligatory to avoid anything that may cause harm or lead to misconduct in human life. Propertys Yogyakarta, as a provider of rental services for lighting and sound systems, sometimes assists and accepts in the organization of events that may lead to misconduct or damage when the events are held. The purpose of this research is to examine how the principles of Maqashid Shariah relate to the events served by Propertys, whether they comply with Maqashid Shariah or not. This study employs a descriptive qualitative research method, using both primary and secondary data sources. It involves field research with observation, interviews, and documentation as data collection techniques. The findings reveal that Propertys Yogyakarta utilizes the ijarah contract in accepting and servicing various types of events while rejecting events or productions that pose a risk of material loss and endanger the safety of the Propertys Yogyakarta team. However, in its service, Propertys does not provide specific provisions regarding the preservation and maintenance of Islamic values ​​in events. The conclusion of this research indicates that there are still some events or activities accepted and served by Propertys Yogyakarta that may cause harmful consequences (mafsadat) which should be rejected in order to preserve and maintain the Maqashid Shariah in terms of preserving religion and wealth.